Carbonylation of o-phenylenediamines with CO2 to 2-benzimidazolones catalyzed by alumina. (27th April 2022) - Matsuo, Hideaki; Choi, Jun-Chul; Fujitani, Tadahiro; Fujita, Ken-ichi
Graphical abstract: Highlights: Alumina catalyzed the carbonylation of o -phenylenediamines with CO2 . This catalytic conversion could be applied to various diamine derivatives. The alumina catalyst was recovered by filtration and could be reused repeatedly. Abstract: Biological carbon fixation can convert carbon dioxide (CO2 ) into chemicals with a variety of uses, and has thus attracted considerable attention, as CO2 is nonhazardous, inflammable and plentiful in the environment. We report here that alumina (Al2 O3 ) can by itself catalyze the carbonylation of o -phenylenediamines with CO2 to produce 2-benzimidazolones. Such alumina-catalyzed carbonylation with CO2 is applicable to various diamine derivatives to provide the corresponding cyclic ureas. Following the reaction, the alumina catalyst is also advantageous in that it can be filtered, accumulated, and reused.